Hansas Christianas Andersenas : pastangos (at)pažinti Hans Christian Andersen : towards the (re)cognition - Gustaitienė, Asta (Vytautas Magnus University, 2009)
The book consists of two parts. The first one focuses on the personality of Hans Christian Andersen, the originality of his works and its preconditions. The author concentrates on Andersens autobiographies pointing out the peculiarities of Andersen's character, the expression of his sexuality and belief in God, also, investigates small prose from the standpoint of genre specifics, analyses the component of simple speaking as poetic strategy and inquires into the correlation of small prose and the tradition of folklore. The second part of the book focuses on Andersen's works from the standpoint of comparative science relating them to the works of modern Scandinavian writers, also, the works of Lithuanian writers, especially those written on the verge of 19th - 20th c., besides, it reveals Andersen's impact on the development of Lithuanian literary fairy tale and artistic expression in the works meant for adults.